Recent Genetic Gains in Nitrogen Use Efficiency in Oilseed Rape - Stahl, Andreas; Pfeifer, Mara; Frisch, Matthias; Wittkop, Benjamin; Snowdon, Rod J. (Frontiers in Plant Science, 2017)
Nitrogen is essential for plant growth, and N fertilization allows farmers to obtain high yields and produce sufficient agricultural commodities. On the other hand, nitrogen losses potentially cause adverse effects to ecosystems and to human health. Increasing nitrogen use efficiency is vital to solve the conflict between productivity, to secure the demand of a growing world population, and the protection of the environment. To ensure this, genetic improvement is considered to be a paramount aspect toward ecofriendly crop production. Winter oilseed rape (Brassica napus L.) is the second most important oilseed crop in the world and is cultivated in many regions across the temperate zones. To our knowledge, this study reports the most comprehensive field-based data generated to date for an empirical evaluation of genetic improvement in winter oilseed rape varieties under two divergent nitrogen fertilization levels. A collection of 30 elite varieties registered between 1989 and 2014, including hybrids and open pollinated varieties, was tested in a two-year experiment in 10 environments across Germany for changes in seed yield and seed quality traits. Furthermore, nitrogen use efficiency was calculated. We observed a highly significant genetics-driven increase in seed yield per se and, thus, increased NUE at both nitrogen fertilization levels. On average, seed yield from modern open-pollinated varieties and modern hybrids was higher than from old open-pollinated varieties and old hybrids. The annual yield progress across all tested varieties was approximately 35 kg ha-1 year-1 at low nitrogen and 45 kg ha-1 year-1 under high nitrogen fertilization. Furthermore, in modern varieties an increased oil concentration and decreased protein concentration was observed. Despite the significant effects of nitrogen fertilization, a surprisingly low average seed yield gap of 180 kg N ha-1 was noted between high and low nitrogen fertilization. Due to contrary effects of N fertilization on seed yield per se and seed oil concentration an oil yield of 2.04 t ha-1 was measured at both N levels. Collectively, the data reveal that genetic improvement through modern breeding techniques in conjunction with reduced N fertilizer inputs has a tremendous potential to increase NUE of oilseed rape.